Perilaku Prososial Etnis Jawa dan Etnis Cina - Basti Basti (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2007)
Purpose of this research is to compare prosocial behavior between two ethnics, Javanese and Chinese. Hypotheses proposed that there’s prosocial behaviors differences between those two ethnic, the Javanese prosocial behavior is higher than Chinese. Subjects participated in this research were 184 Javanese and Chinese who live in Jogjakarta. Prosocial behavior scale is used as the research tool.Data analyzed through two way Anova result F 13.048 with p <.01. This result proof that prosocial behavior between Javanese and Chinese is very significantly different. The mean score of prosocial behavior from Javaneese is 143,489 and Chinese is 137,271. It means that Javanese’s prosocial behavior is higher than the Chinese. Keywords : Prosocial Behavior, Javanese Ethnicity, Chinese Ethnicity.